THE EFFECT OF QUESTION–ANSWER RELATIONSHIP (QAR) STRATEGY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMK N 1 MINAS IN COMPREHENDING RECOUNT TEXTS - Sandy Fazri Muhammad; Eliwarti Eliwarti; Afrianto Afrianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aimes to find out whether there is a significant effect of using Question – Answer Relationship strategy on the ability of the first year students of SMK N 1 Minas in comprehending recount texts. The research design is a pre-experimental research with one group pre-test and post-test dessign. The sample was X TITL (Teknik Instalasi Tenaga Listrik) chosen by using cluster random sampling technique. The result of the data analysis show that the scores of the pre-test was 64.37 and the mean score of the post-test was 71.77. In other words, the mean scores of the post-test is higher than the pre-test. The result also showed that the value of t-obs is higher than t-table (8.351 > 2.043). It can be concluded that the Alternative Hypothesis (Ha) is accepted and Null Hypothesis (Ho) is rejected. Hence, there is a significant effect of Question – Answer Relationship strategy on the ability of the first year students of smk n 1 minas in comprehending recount texts.Key Words: Effect, Question – Answer Relationship, Reading Comprehension, Recount Texts.